Not enough : human rights in an unequal world - Moyn, Samuel (The Belknap Press of Harvard University Press, 2019)
The age of human rights has been kindest to the rich. As state violations of political rights garnered attention, a commitment to material equality disappeared and market fundamentalism emerged as the dominant economic force. Samuel Moyn asks why we chose not to challenge wealth and neglected the demands of a broader social and economic justice.--